Metaphor in the Bible - Gevorgyan, Gourgen (Armenian Folia Anglistika, 2006)
Metaphor as a stylistic device is widely used in fiction. Writers can usually be easily identified due to the metaphors they use in their works. Metaphor is one of the basic devices of imagery. The Bible abounds in metaphors and the system of imagery in the Holy Book is heavily dependent on this device. Here, metaphors appear not only in the form of words, but of sentences, as well. Symbols, which are specific to the Bible, communicate a special meaning to the events and phenomena described.